STRUCTURAL MANAGEMENT PARADIGM IN THE MODELS OF NETWORK ORGANIZATIONS (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2021)
Development problem of network organizations’ modelling methods is considered in this article. It is characterized with two fundamental directions that are the basis of the scientific approach. The authors offer one more aspect of modelling – taking into account the influence on the object’s structure and the produced products of external messages that carry structural rules, i. e. the rules needed for similar objects modelling.